Fasting and meal-related zonulin serum levels in a large cohort of obese children and adolescents - Pepe, Giorgia; Corica, Domenico; Currò, Monica; Aversa, Tommaso; Alibrandi, Angela; Ientile, Riccardo; Caccamo, Daniela; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2024)
Zonulin recently emerged as a valuable biological marker to assess the integrity of the intestinal mucosal barrier. Nevertheless, data about zonulin in pediatric age are extremely scarce.Aim of this study was to investigate the relationship between serum zonulin levels, both fasting and postprandial, with body mass index (BMI) and biochemical markers of insulin resistance (IR), insulin sensitivity, β-cell function and cardio-metabolic risk in obese nondiabetic youths.One hundred and four children and adolescents with obesity (BMI ≥ 2.0 SDS) were enrolled (mean age 11.43±2.66). All the patients underwent clinical and biochemical assessment, including oral glucose tolerance test (OGTT) and liver ultrasonography.Zonulin serum levels were measured at fasting state, at 60-minute and 120-minute OGTT timepoint. Impaired fasting glycaemia and impaired glucose tolerance were documented in 27.9% and 11.5% of patients, respectively. IR was documented in 69.2% of cases.Liver steatosis was diagnosed in 39.4%. Zonulin serum levels significantly increased from baseline to 60-minute and 120-minute OGTT timepoint (p<0.001) in the entire study population. A positive correlation between BMI SDS and serum zonulin levels at 120minute OGTT timepoint (p<0.05) was documented. Multiple linear regression analysis highlighted a positive association of zonulin fasting levels with IR and glutamicoxalacetic transaminase levels (GOT, p<0.05). No significant differences in zonulin levels were demonstrated for age, sex, pubertal status, glucose, lipid profile and the other obesity-related parameters.Our results show, for the first time in a pediatric cohort, the meal-related pattern of secretion of serum zonulin, which tends to significantly increase during and at 2-hours postprandial assessment. Even if the underlying mechanisms associating intestinal permeability and obesity have not been fully elucidated yet, our data confirm a close relationship between zonulin concentration and obesity in pediatric population. IR seems to significantly influence zonulin serum levels, thus a central role of IR in this pathway is conceivable.